2012
DOI: 10.1027/1618-3169/a000125
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search Facilitation in Repeated Displays Depends on Visuospatial Working Memory

Abstract: When distractor configurations are repeated over time, visual search becomes more efficient, even if participants are unaware of the repetition. This contextual cueing is a form of incidental, implicit learning. One might therefore expect that contextual cueing does not (or only minimally) rely on working memory resources. This, however, is debated in the literature. We investigated contextual cueing under either a visuospatial or a nonspatial (color) visual working memory load. We found that contextual cueing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…Indeed, although both IL and SL phenomena can occur with minimal attentional resources, learning effects are usually weaker than when attention is fully available [1,6,12,77]. CC appears also reduced under high working-memory load provided that a dual-task condition requires significant spatial and concurrent spatial working-memory resources [78,79]. In addition, CC depends on the repeated contexts being attended [80].…”
Section: Mediating Factors In CCmentioning
confidence: 95%
“…Indeed, although both IL and SL phenomena can occur with minimal attentional resources, learning effects are usually weaker than when attention is fully available [1,6,12,77]. CC appears also reduced under high working-memory load provided that a dual-task condition requires significant spatial and concurrent spatial working-memory resources [78,79]. In addition, CC depends on the repeated contexts being attended [80].…”
Section: Mediating Factors In CCmentioning
confidence: 95%
“…However, visual search with a simulated central scotoma is a highly artificial situation and we cannot rule out that contextual cueing was absent because the observers needed to control the exploration of the search display voluntarily in order to compensate for the scotoma. Behavioral tasks in normal observers have shown that contextual cueing, particularly the use of learned memory traces, depends on attentional and working memory capacity (Jiang & Leung, 2005;Manginelli, Geringswald, & Pollmann, 2012;Manginelli, Langer, Klose, & Pollmann, 2013;Travis, Mattingley, & Dux, 2012;Vickery, Sussman, & Jiang, 2010). A cumbersome top-down controlled exploration of search displays forced by a simulated scotoma may leave not enough capacity to use contextual cues for attentional guidance in repeated displays.…”
Section: Introductionmentioning
confidence: 97%
“…The information to be memorized in Experiment 2a was the color of each item contained in the working memory array, while the locations were irrelevant (and kept constant). In a previous pilot study with four items, we observed that this kind of task is more demanding than the corresponding spatial version (see also Manginelli et al, 2012). Therefore, we decided to reduce the size of the memory array in order to achieve performance comparable to that with visuospatial tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it was concluded that repeated configurations could be learned under the working memory load of a secondary task. In a study from our lab, the loss of search facilitation for repeated displays was observed when a concurrent visuospatial working memory load was applied (Manginelli et al, 2012). This elimination of contextual cueing was selective for visuospatial working memory load; it did not occur when a nonspatial (color) working memory load was added.…”
mentioning
confidence: 99%
See 1 more Smart Citation